Aspek Yuridis Hak Atas Tanah di Atas Laut Menurut Undang-Undang Pokok Agraria - Shafa Naura Rahmanissa; Indra Yuliawan; Arista Chandra Irawati (Jurnal Hukum Caraka Justitia, 2026)
Among the types of land rights are Ownership Rights and Building Use Rights. Naturally, the object of these rights is a parcel of land. However, in the Bhumi application owned by ATR/BPN, there have been findings of Ownership Rights and Building Use Rights certificates in the water areas of Sidoarjo and Tangerang. This discovery raises questions about how land rights objects can be used for objects above the seawaters in Indonesia. According to Law Number 5 of 1960 concerning Basic Agrarian Principles, land rights certificates are used for the earth's surface, subsurface, and water above and within the earth, as well as the space above the earth’s surface with applicable legal provisions. If the land contains natural resources within the territory of the Indonesian state, there are specific regulations that govern it. This study aims to analyze the validity of the issuance of certificates as proof of land rights used for objects in water areas. Harmonization of each regulation is also needed to prevent overlaps between higher and lower regulations, as outlined in the hierarchy of laws. Therefore, issuing land rights certificates for management rights over water areas is illegal. The method employed in this research is a normative-empirical approach, examining existing legal bases and regulations and comparing them with empirical implementations in reality.